Efektivitas Metode Pelatihan Berbasis Konsep Patient Centered Care Terhadap Pengetahuan dan Sikap Profesional Pemberi Asuhan (PPA) di RS Untan Pontianak - Nisa, Khairun; Hadi, Hamam; Nurunniyah, Siti (SPT. haria Journal and Education Center Publishing, 2026)
Background: Healthcare in Indonesia faces critical issues in clinical interaction, where many Healthcare Professionals (PPA) have not fully implemented Patient-Centered Care (PCC). This failure directly results in low patient satisfaction, increased complaints, and even clinical therapy failure risks. At RS UNTAN Pontianak, this challenge is amplified by suboptimal human resource readiness and an incomplete understanding of PCC concepts. Objective: To analyze the effectiveness of PCC-based training methods on improving PPA knowledge and attitudes in the inpatient ward of RS UNTAN Pontianak. Methods: A quantitative quasi-experimental pre-post test design involving 58 PPAs across three groups: Presentation+Simulation, Presentation+Video, and conventional control (Presentation only). Data were collected using a PCC knowledge questionnaire and an attitude scale, analyzed using paired t-test, ANOVA, and multiple regression (α=0.05). Results: The Presentation + Simulation method showed the highest score improvements for both knowledge (increase of 22.63 points) and attitude (increase of 12.00 points), and was significantly superior to the Presentation + Video and Conventional Presentation methods. The path coefficient for the simulation group was 1.376 for knowledge (R²=47.3%) and 1.616 for attitude (R²=65.3%). Conclusion: Interactive and experiential training, particularly simulation, is the most effective method for improving PCC competencies among PPAs. Hospitals should prioritize practice-based training methods for successful PCC implementation.